2012
DOI: 10.1074/jbc.m112.399428
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylserine Decarboxylase 1 (Psd1) Promotes Mitochondrial Fusion by Regulating the Biophysical Properties of the Mitochondrial Membrane and Alternative Topogenesis of Mitochondrial Genome Maintenance Protein 1 (Mgm1)

Abstract: Background: Phosphatidylethanolamine is proposed to regulate mitochondrial fusion, but its mechanism of action is unknown. Results: Decreasing phosphatidylethanolamine reduces the rate of lipid mixing and the biogenesis of Mgm1, a mitochondrial fusion protein. Conclusion:Psd1 regulates the lipid and protein machineries of mitochondrial fusion. Significance: Understanding how lipid metabolism regulates mitochondrial dynamics will reveal its role in cellular functions such as apoptosis and autophagy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
87
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 34 publications
6
87
0
1
Order By: Relevance
“…Furthermore, confocal fluorescence microscopy showed that mitochondrial fragmentation was greatly increased in mtPE-deficient cells compared with control cells, as was previously observed in Pisd Ϫ/Ϫ embryonic fibroblasts (1). In yeast, elimination of mtPE synthesis (85) or concomitant loss of synthesis of both CL and PE also promotes mitochondrial fragmentation (52). Mitochondrial morphology and function are closely linked, and mitochondrial dysfunction can induce autophagy/mitophagy and mitochondrial fragmentation (86 -88).…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Furthermore, confocal fluorescence microscopy showed that mitochondrial fragmentation was greatly increased in mtPE-deficient cells compared with control cells, as was previously observed in Pisd Ϫ/Ϫ embryonic fibroblasts (1). In yeast, elimination of mtPE synthesis (85) or concomitant loss of synthesis of both CL and PE also promotes mitochondrial fragmentation (52). Mitochondrial morphology and function are closely linked, and mitochondrial dysfunction can induce autophagy/mitophagy and mitochondrial fragmentation (86 -88).…”
Section: Discussionsupporting
confidence: 66%
“…Mitochondrial morphology and function are closely linked, and mitochondrial dysfunction can induce autophagy/mitophagy and mitochondrial fragmentation (86 -88). Defects in mitochondrial fusion, ATP synthesis, and cell growth occur in mammalian cells lacking the mitochondrial fusion factors Mfn1 and Mfn2, and in cells with reduced amounts of the fusion factor Opa1 (66,85). It is unlikely, however, that the extensive mitochondrial fragmentation in Pisd KD#1 cells is primarily due to deficiency of fusion factors because amounts of Mfn1, Mfn2, and Opa1 are equivalent in Pisd KD#1 and NegCtrl cells, nor is it likely that the widespread mitochondrial fragmentation in PSB-2 cells is due to reduced amounts of Mfn1 or Mfn2 because Mfn1 is equally abundant in PSB-2 and WT cells, and Mfn2 is slightly increased.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When only short MGM1 is introduced into PCP1 deletion strains of yeast mitochondrial morphology is partially restored and prevents loss of mitochondrial DNA caused by defective mitochondrial fusion. In yeast, the balance between long and short forms of MGM1 is also regulated by PSD1, a phosphatidylserine decarboxylase, in the IMM that produces phosphatidylethanolamine, indicating regulation of MGM1 processing by mitochondrial lipid composition and indicating the activity of PCP1 is regulated by lipid composition [45] (Figure 1 and 2).…”
Section: Inner Mitochondrial Membrane Fission and Fusionmentioning
confidence: 99%